Resistance exercises in peripheral arterial diseased elders - Câmara, Lucas Caseri; Santarém Sobrinho, José Maria; Jacob Filho, Wilson; Kuwakino, Marcelo Hisato (Acta Fisiátrica, 2006)
The aging of the world population has provoked an increase of chronic degenerative diseases, facing the scientific community with the challenge to search and choose the best and most feasible treatments. Peripheral arterial disease, which appears as a complication of arteriosclerosis, shows increased and continuous incidence as age progresses, therefore adding to several other diseases that ensue this portion of the population. The conclusive evidence of efficiency and cost-benefits in the use of exercise as a primary indication for the treatment of aging patients has become an excellent alternative for this population group, which already uses various medications due to other chronic diseases. The benefits of resistance exercise still have not been fully explored as an isolated treatment for peripheral arterial disease in aged persons, however has already indicated that this form of exercising can and should be used for the treatment of the referred pathology, since it can reverts or delays the associated degenerative alterations which commits their carriers, diminishing significantly the many limitations imposed by the disease in association with sedentary aging